The Effect of the Quality of Financial Statements and Access to Financing on the Performance of MSMEs in Indonesia - Haliana Haliana; Endarwati Endarwati (Universitas KH. Abdul Chalim Mojokerto, 2026)
Micro, small, and medium enterprises (MSMEs) have a strategic role in the Indonesian economy, but still face obstacles in financial reporting and access to financing that have an impact on business performance. This research is important because the results of previous studies showed inconsistency and did not study many variables at the same time, especially in the Special Region of Yogyakarta. This study aims to analyze the influence of the quality of financial statements and access to financing on the performance of MSMEs in the Special Region of Yogyakarta. This study uses a quantitative approach through a survey of 150 MSME respondents in Yogyakarta, which was analyzed using multiple linear regression analysis with the help of SPSS. The results showed that the quality of financial statements and access to financing had a significant effect on the performance of MSMEs (p < 0.05). The value of the regression coefficient for the quality of financial statements was 0.393 and access to financing was 0.461. Simultaneously, the two variables explain the 50.2% variation in MSME performance (Adjusted R² = 0.502). Thus, it can be concluded that the quality of financial statements and access to financing significantly improve the performance of MSMEs in the Special Region of Yogyakarta.